Extens??o da Arquitetura NovaGenesis para Cen??rios de IoT em Redes LPWAN utilizando LoRa - Bonomo, Epper Epper (2022)
This Master Thesis expands previous works to improve the Future Internet Architec ture (FIA) called NovaGenesis regarding Internet of Things (IoT) scenarios, specially for Low Power Wide Area Network (LPWAN) applications. First, the basic concepts necessary to understand NovaGenesis, as well as the fundamental characteristics of the Longe Range (LoRa) communication technology will be briefly discussed. This Thesis extends NovaGenesis for LoRa integration, updating its embedded version, developing, and configuring the required Operational System and device resources. Afterwards, an experimental evaluation scenario is proposed in order to prove the benefits of NovaGenesis with LoRa for IoT. The evidence collected from the laboratory tests subsidize and prove the feasibility of implementing a FIA on a LPWAN with low throughput capacity and packet loss. The performance of the architecture proposed for this proof of concept (PoC) was evaluated and its offenders were identified, all sta ges of the NovaGenesis lifecycle for the IoT node called Embedded Proxy Gateway Service (EPGS) were validated, ensuring the continuity of the service, as well as the service level delivered by NovaGenesis to a data application. The results obtained from the tests demonstrated the feasibility of integrating an FIA NG into a LoRa network, where the elements of the NG proved to be flexible and transparent for the proposed architecture to prove this hypothesis. To the best of our knowledge, this is the first time LoRa is integrated with a FIA, evaluating its performance. Finally, the points still open for future work and the conclusion of this article are delimited.